A Typology of Moral Positionality for Educational Administrators. Issue 4 (2nd October 2017) - O'Brien, Jonathan J.
Abstract: This qualitative study explored educational leaders' conduct in self-reported critical incidents ( n = 50). Incidents were analyzed for participants' orientations to self or others and professional values, and assigned to one of four position types: authority, equity, compliance, or strategy. The typology categorizes participants' ethical actions while attributing their conduct to moral courage. Implications for research and practice are discussed.